2018
DOI: 10.1111/mms.12547
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic variation in diet and habitat of Irrawaddy dolphins (Orcaella brevirostris) in the Gulf of Thailand and the Andaman Sea

Abstract: Irrawaddy dolphins (Orcaella brevirostris) are threatened, little‐known cetaceans primarily jeopardized by fishing gear entanglement. Information regarding life history, foraging ecology, and movement are crucial to determine management units and conservation regions. This is the first analysis of the ontogenetic changes in diet and habitat of Irrawaddy dolphins from the Gulf of Thailand and the Andaman Sea using stable isotopes from skin and teeth. Results suggest limited age and sex structure indicated by we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 100 publications
(107 reference statements)
1
11
0
Order By: Relevance
“…Overall, genetic differentiation among geographic regions was statistically significant based on mtDNA and microsatellite analyses. Our results are consistent with statistical differences in average stable isotope values reported from O. brevirostris teeth in the same regions by Jackson-Ricketts et al (2018 ), indicating distinct geographic groups (Eastern Gulf, Northern Gulf, Western Gulf, and Andaman Sea) may exist in Thailand’s waters. However, no significant difference was detected for average tooth stable isotope values between northern and western Gulf regions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Overall, genetic differentiation among geographic regions was statistically significant based on mtDNA and microsatellite analyses. Our results are consistent with statistical differences in average stable isotope values reported from O. brevirostris teeth in the same regions by Jackson-Ricketts et al (2018 ), indicating distinct geographic groups (Eastern Gulf, Northern Gulf, Western Gulf, and Andaman Sea) may exist in Thailand’s waters. However, no significant difference was detected for average tooth stable isotope values between northern and western Gulf regions.…”
Section: Discussionsupporting
confidence: 91%
“…Geographic coordinates for all except one individual from Phetchaburi were recorded at the time of collection. Samples were grouped into four general regions as described in Jackson-Ricketts et al (2018 ), each region encompassing specific sites: (1) Mueang Trat, representing the eastern Gulf of Thailand (EG, n = 11), (2) Chonburi, Chachengsao, Samut Sakorn, and Phetchaburi, making up the northern Gulf (NG, n = 12), (3) Chumporn and Surattani, making up the western Gulf (WG, n = 9), and (4) Trang and Satun, representing Andaman Sea sites (AS, n = 5) ( Figure 1 ). Genomic DNA from minced tissue samples was extracted using DNeasy blood and tissue extraction kits (QIAGEN, Valencia, USA) according to the manufacturer instructions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the dietary studies of Orcaella dolphins have been limited to either the freshwater populations of the Irrawaddy dolphin (Adulyanukosol, ; Baird & Mounsouphom, ; Marsh, Lloze, Heinsohn, & Kasuya, ; Smith, Tun, Chit, Win, & Moe, ) or the Australian snubfin dolphin, Orcaella heinsohni (Parra, ; Parra & Jedensjö, ); however, Ponnampalam et al () observed Irrawaddy dolphins in the eastern Gulf of Thailand foraging for cephalopods, as indicated by the presence of squid ink and detached squid tentacles at the water surface. Results from a stable isotope study by Jackson‐Ricketts et al () indicated that Irrawaddy dolphins in the eastern Gulf of Thailand primarily consumed ponyfish ( Nuchequula sp. ), mackerels ( Rastrelliger spp.…”
Section: Discussionmentioning
confidence: 99%